A comparison of verification in the temporal and cepstrum-transformed domains of Transient Evoked Otoacoustic Emissions for biometric identification. (1st January 2011) - Chambers, Paul; Grabham, Neil J.; Swabey, Matthew A.; Lutman, Mark E.; White, Neil M.; Chad, John E.; Beeby, Stephen P.
An investigation of methods for the use of Transient Evoked Otoacoustic Emissions (TEOAE) as an identification biometric is described in this paper. Three methods to calculate the Euclidean distance between individuals are investigated: Interpretation of area-under-the-curve information from time-series TEOAE; Measurement in the temporal domain between a TEOAE and reference template; Measurement in the cepstral domain between a TEOAE and reference template. False acception and rejection rates (FAR&FRR) are given for test data. In this study maximal performance was given by the temporal domain Euclidian distance, giving 1.27%FAR and 0%FRR for a data set with 230 recordings from 23 subjects.